SIFO 1993: Six out of ten youngsters against the EC - Swedish Institute of Public Opinion Research; Göteborgs-Posten (Swedish Institute of Public Opinion Research, 1994)
The Swedish Institute of Public Opinion Research (SIFO) carried out this survey at the request of the daily paper Göteborgs-Posten. The special topics of this survey are EC, EES and EU. The respondents were asked if they had a definite idea about the differences between the European Economic Space (EES), the European Communities (EC) and the European Union (EU). They were also asked about the name of the agreeement concluded by the EFTA- and EC-countries; opinion on the way the negotiation about a Swedish EC-membership has been handled so far; most important issues for the negotiations about a membership; opinion on a Swedish EC-membership and if they believed that the Swedish negotiators look after the interests of the Swedish people. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, income and party voted for in the general election 1991.

Svenska institutet för opinionsundersökningar genomförde denna undersökning på begäran av dagstidningen Göteborgs Posten. Ämnet för denna undersökning är EG, EES och EU. Respondenterna ställdes frågan om de hade en klar uppfattning om skillnaden mellan EG, EES och EU. De ställdes också frågan om namnet på avtalet som slutits mellan EG och EFTA länderna, sina åsikter om hur förhandlingarna av svenskt EG medlemskap, de viktigaste frågorna i förhandlingarna om ett medlemskap, åsikter om ett medlemskap i EG och om de ansåg att de svenska förhandlarna tog till vara på svenska folkets intressen. Bakgrundsvariabler inkluderar kön, bostadsort, ålder, svenskt medborgarskap, yrke, privat eller offentlig sektor, medlemskap i fackförening, inkomst och vilket parti som de röstat för i de allmänna valen 1991.
SIFO 1993: Sex av tio unga negativa till EG
Keywords: International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap